Using implementation mapping to develop strategies for preventing non-communicable diseases in Japanese small- and medium-sized enterprises - Odawara, Miyuki; Saito, Junko; Yaguchi-Saito, Akiko; Fujimori, Maiko; Uchitomi, Yosuke; Shimazu, Taichi (Frontiers in Public Health, 2022)
Introduction: Workplace programs to prevent noncommunicable diseases (NCD) in the workplace can help prevent the incidence of chronic diseases among employees, provide health benefits, and reduce the risk of financial loss. Nevertheless, these programs are not fully implemented, particularly in small- and medium-sized enterprises (SMEs). The purpose of this study is to develop implementation strategies for health promotion activities to prevent NCDs in Japanese SMEs using implementation mapping (IM) to present the process in a systematic, transparent, and replicable manner. Methods: We examined IM tasks 2 and 3 based on the results of the interviews with 15 SMEs to develop implementation strategies that are appropriate for the Japanese culture and the needs of SMEs. Results: In task 2 of the IM, we identified performance objectives, determinants, and change objectives for each implementation stage: adoption, implementation, and maintenance; to identify the actors needed to be involved and actions necessary to enhance implementation effectiveness. Twenty-two performance objectives were identified in each implementation stage. In task 3 of the IM, the planning group matched behavior change methods (e.g., modeling and setting of graded tasks, framing, self-reevaluation, and environmental reevaluation) to meet performance objectives. We used a consolidated framework for implementation research to select the optimal behavioral change technique for performance objectives and determinants and designed a practical application. A final strategies list was compiled and presented to the planning team for consensus; the planning team agreed on the inclusion of sixteen strategies in the overall implementation plan design. Discussion: This paper provides implementation strategies for NCD prevention in SMEs following an IM protocol. Although the identified implementation strategies might not generalize to all SMEs planning health promotion activities implementation, because they were tailored to contextual factors identified in formative research, identified performance objectives and implementation strategies can help direct next steps in launching preventive programs against NCD in SMEs.